Identification of receptor-binding domains on human interleukin 5 and design of an interleukin 5-derived receptor antagonist. - Tavernier, J (1995)
A detailed structure-function analysis of human interleukin 5 (hIL5) has been performed. The hIL5 receptor is composed of two different polypeptide chains, the alpha and beta subunits. The alpha subunit alone is sufficient for ligand binding, but association with the beta subunit leads to a 2- to 3-fold increase in binding affinity. The beta chain is shared with the receptors for IL3 and granulocyte/macrophage-colony-stimulating factor--hence the descriptor beta C (C for common). All hIL5 mutants were analyzed in a solid-phase binding assay for hIL5R alpha interaction and in a proliferation assay using IL5-dependent cell lines for receptor-complex activation. Most residues affecting binding to the receptor alpha subunit were clustered in a loop connecting beta-strand 1 and helix B (mutants H38A, K39A, and H41A), in beta-strand 2 (E89A and R91A; weaker effect for E90A) and close to the C terminus (T109A, E110A, W111S, and I112A). Mutations at one position, E13 (Glu13), caused a reduced activation of the hIL5 receptor complex. In the case of E13Q, only 0.05% bioactivity was detected on a hIL5-responsive subclone of the mouse promyelocytic cell line FDC-P1. Moreover, on hIL5-responsive TF1 cells, the same mutant was completely inactive and proved to have antagonistic properties. Interactions of this mutant with both receptor subunits were nevertheless indistinguishable from those of nonmutated hIL5 by crosslinking and Scatchard plot analysis of transfected COS-1 cells.